By His Excellency Edward Viscount Cornbury, Her Majesty's capt. general and governour in chief of the province of New-York ... A proclamation : Whereas I am informed that sundry persons in this province, ill affected to Her Majesties service, have, by harbouring, concealing and conveying away divers, as well of Her Majesties standing land forces, as from the ships of war attending upon this province, by which others are greatly encouraged to desert Her Majesties service now in time of actual war. ... Given at Fort Anne in New-York this fourth day of November, anno Dom. 1703 . (Printed by William Bradford, printer to the Queens Most Excellent Majesty, 1703)
Taking measures to prevent desertion from the army.